Single-sided board of PCB (Printed Circuit Board) and preparation process thereof
By adding modified graphene oxide and modified nanosilicon dioxide to the coating of single-sided panel of PCB board, the problem of prone to cracking of the aqueous epoxy resin coating is solved, and the corrosion resistance and oxidation resistance of the product are significantly improved.
Patent Information
- Application Number
- CN202411622033.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the etching process of existing PCB single-sided panels, the aqueous epoxy resin coating is prone to cracking and has poor density, resulting in corrosive media being easily penetrated and eroding the substrate.
By adding graphene oxide modified by chitosan and polyethylene glycol diglycidyl ether, the corrosion resistance of the coating is improved, and polyvinyl alcohol is used as a curing agent, the problem of coating cracking is solved. At the same time, by blending modified nanosilicon dioxide with polyvinyl alcohol, an antioxidant film liquid is prepared to improve the water resistance of the film.
It significantly improves the corrosion resistance and oxidation resistance of single-sided panels of PCB boards, enhances the density and water resistance of the coating, and extends the service life of the product.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PCB single-sided board manufacturing, in particular to a PCB single-sided board and a preparation process thereof. Background Art
[0002] PCB single-sided board is a kind of printed circuit board. Only one side of the PCB board has circuits, and the other side is a substrate or covered with insulating ink. There are no circuits and the whole board is translucent when placed under strong light. Only the side with circuits contains copper foil in the cross section.
[0003] Chinese patent CN116709647A discloses a process for preparing a printed circuit board, which mainly includes substrate preparation, punching and laminating, exposure and development, etching, film stripping, quality inspection, and solder resist.
[0004] During etching, reagents are needed to corrode the excess copper skin, and the copper skin on the circuit with ink is retained, so the ink needs to have good anti-corrosion performance. Therefore, we propose a single-sided PCB board and its preparation process. Summary of the invention
[0005] The object of the present invention is to provide a single-sided PCB board and a preparation process thereof to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solution: A preparation process of a single-sided PCB board, mainly comprising the following steps:
[0007] S1: Substrate preparation: Clean the cut copper-clad laminate to remove dust and burrs from its surface to obtain a substrate;
[0008] S2: Drilling positioning holes: Drilling registration holes at the four corners of the substrate and opening circuit holes according to the circuit design;
[0009] S3: Silk screen circuit: Print the circuit diagram on the copper side of the substrate with anti-corrosion ink;
[0010] S4: Etching: Immerse the printed circuit board in an etchant, stir, and corrode the exposed copper to obtain the circuit layout;
[0011] S5: Solder resist: clean the etched substrate, wipe off the moisture, screen print the green solder resist, and dry;
[0012] S6: Quality inspection: The circuit layout on the substrate obtained in S5 is inspected by optical instruments to remove unqualified products;
[0013] S7: Anti-oxidation: Clean and dry the substrate that has passed the quality inspection, then apply a layer of anti-oxidation film liquid on the surface, dry it into a film, and obtain a PCB single panel.
[0014] Furthermore, the etching agent in S4 is copper etching solution, model: Q / YS.115, from Guangzhou Yishun Chemical Co., Ltd.;
[0015] The green oil solder resist model in S5 is: CW3300G, which comes from Shanghai Gushuo Electronic Technology Co., Ltd.
[0016] Furthermore, the process conditions for drying in S5 are: temperature: 145-155° C., duration: 55-65 s.
[0017] Furthermore, the process conditions for drying in S7 are: temperature: 70-110° C., duration: 1.5-3.5 h;
[0018] The process conditions for drying and film formation are: temperature: 110-115°C, time: 2-4h.
[0019] Furthermore, the anti-corrosion ink described in S3 is prepared by mixing modified graphene oxide, polyvinyl alcohol solution, water-based epoxy resin and pigment, and the specific process is as follows:
[0020] The modified graphene oxide, polyvinyl alcohol solution, water-based epoxy resin and pigment are mixed in a mass ratio of (2-4):(2-4):(1-3):1, and stirred on a magnetic stirrer to obtain an anti-corrosion ink.
[0021] Furthermore, the process conditions for stirring with a magnetic stirrer are: temperature: 50-60°C, duration: 30-40min, and rotation speed: 200-300r / min.
[0022] Furthermore, the mass fraction of the polyvinyl alcohol solution is 4%, the polyvinyl alcohol CAS number is 9002-89-5, and it is sourced from Nanjing Chemical Reagent Co., Ltd.
[0023] Furthermore, the waterborne epoxy resin model is E-51, and the epoxy value is 0.48-0.54; it comes from Jiangyin Shunsheng Composite Materials Co., Ltd.
[0024] Furthermore, the pigment is sourced from Shenzhen Daxing Chemical Co., Ltd.
[0025] Furthermore, the modified graphene oxide is obtained by grafting chitosan and polyethylene glycol diglycidyl ether, and the specific process is as follows:
[0026] The graphene oxide and deionized water are mixed, ultrasonically treated for 1 to 2 hours until uniformly dispersed, and then chitosan solution is added, stirred and reacted on a magnetic stirrer. After the reaction is completed, the mixture is washed with deionized water until the pH is neutral, and freeze-dried to obtain chitosan-modified graphene oxide powder; the chitosan-modified graphene oxide powder is added to a polyethylene glycol diglycidyl ether solution, ultrasonically dispersed for 0.5 to 1.5 hours, refluxed, taken out, washed with deionized water for 3 to 5 times, and freeze-dried to obtain modified graphene oxide.
[0027] Furthermore, the chitosan solution preparation process is as follows:
[0028] Chitosan and acetic acid solution are mixed in a mass ratio of 1: (40-50), and stirred until completely dissolved to obtain a chitosan solution.
[0029] Furthermore, the mass ratio of graphene oxide, deionized water, and chitosan solution is 1:(90-100):(10-20).
[0030] Furthermore, the mass ratio of chitosan modified graphene oxide powder to polyethylene glycol diglycidyl ether solution is 1:(90-100).
[0031] Furthermore, the freeze-drying process conditions are: temperature: -10 to -20°C, time: 20 to 24 hours.
[0032] Furthermore, the temperature of the magnetic stirrer is 40-50°C, the time is 10-16h, and the speed is 300-500r / min.
[0033] Furthermore, the reflux process conditions are: temperature: 65-85°C, time: 4-6h.
[0034] Further, graphene oxide, particle size: 10-20 μm, comes from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;
[0035] The mass fraction of acetic acid solution is 2%, acetic acid CAS number: 64-19-7, from Merck reagent;
[0036] The mass fraction of polyethylene glycol diglycidyl ether solution is 1%, CAS number: 26403-72-5, and it comes from Shanghai Yuanye Biotechnology Co., Ltd.
[0037] In the above technical solution, waterborne epoxy resin will crack during the curing process, and the density of the formed coating is poor, which makes it easy for the corrosive medium to penetrate the coating and corrode the substrate. Therefore, adding graphene oxide modified by chitosan and polyethylene glycol diglycidyl ether can improve the corrosion resistance of the coating. At the same time, using polyvinyl alcohol as a curing agent solves the problem of easy cracking of waterborne epoxy resin coating. In addition, the hydroxyl and amino groups of chitosan and the epoxy groups of polyethylene glycol diglycidyl ether can form a variety of covalent connections with graphene oxide, further improving the coating's resistance to corrosive media.
[0038] Furthermore, the antioxidant film liquid in S7 is prepared by blending modified nano-silicon dioxide and polyvinyl alcohol, and the specific process is as follows:
[0039] The polyvinyl alcohol and distilled water are mixed in a mass ratio of 1: (30-40), and magnetically stirred to completely dissolve them. Then, the modified nano-silicon dioxide is added, and magnetically stirred. After stirring evenly, ultrasonication is performed for 25-35 minutes to obtain an antioxidant film liquid.
[0040] Furthermore, the mass ratio of polyvinyl alcohol to modified nano-silicon dioxide is 1:(0.3-0.5).
[0041] Furthermore, the process conditions of magnetic stirring are: temperature: 45-55°C, duration: 55-65min, rotation speed: 400-500r / min.
[0042] Furthermore, polyvinyl alcohol CAS number: 9002-89-5, comes from Guangzhou Hongzhou Chemical Co., Ltd.
[0043] Furthermore, the modified nano-silica is prepared from a silane coupling agent and nano-silica, and the specific process is as follows:
[0044] Mix nano-silica and anhydrous ethanol in a mass ratio of 1: (20-30), stir evenly to obtain a mixed solution, then add a silane coupling agent, stir evenly, and reflux. After the reaction is completed, wash and filter repeatedly with anhydrous ethanol until the filtrate is clear and transparent. After the filter cake is dried, grind it into powder to obtain modified nano-silica.
[0045] Furthermore, the mass ratio of the mixed solution to the silane coupling agent is 1:(3-5).
[0046] Furthermore, the reflux process conditions are: temperature: 65-75°C, time: 2.5-3.5h.
[0047] Furthermore, the drying process conditions are: temperature: 70-80°C, time: 3-5h.
[0048] Furthermore, the silane coupling agent is KH550, which is added in the form of an aqueous solution with a mass fraction of 50%, and is sourced from Yunsheng Chemical (Shandong) Co., Ltd.;
[0049] Nano-silicon dioxide CAS number: 7631-86-9, particle size: 20nm, purity: 99%, from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;
[0050] Anhydrous ethanol CAS number: 64-17-5, from Jinan Dianhua Chemical Technology Co., Ltd.
[0051] In the above technical solution, the silane coupling agent is hydrolyzed to generate silanol, which condenses with the hydroxyl groups on the surface of nano-silicon dioxide to generate silicon-oxygen bonds, which can effectively prevent the aggregation of particles and improve the dispersibility. Polyvinyl alcohol has good compatibility, heat resistance, and film-forming properties, but because polyvinyl alcohol molecules contain hydroxyl groups, they are easy to absorb water and regain moisture in a humid environment, affecting the service life of the product. After adding modified nano-silicon dioxide, the modified silicon dioxide nanoparticles can be evenly dispersed in the matrix, filling the gaps, making the structure more tightly arranged, enhancing the intermolecular force, making it difficult for water molecules to enter, and improving the water resistance of the film.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] 1. Various covalent connections are constructed between the hydroxyl group, amino group of chitosan and the epoxy group of polyethylene glycol diglycidyl ether and graphene oxide. Chitosan and polyethylene glycol diglycidyl ether are grafted onto the surface of graphene oxide and blended with water-based epoxy resin to further enhance the coating's resistance to corrosive media. At the same time, polyvinyl alcohol is used as a curing agent to solve the problem of easy cracking of water-based epoxy resin coatings.
[0054] 2. Nano-silica is modified by silane coupling agent to effectively prevent the agglomeration of particles and improve dispersibility. After mixing with polyvinyl alcohol, the modified silica nanoparticles are evenly dispersed in the matrix, filling the gaps, making the structure more tightly arranged, enhancing the intermolecular force, making it difficult for water molecules to enter, and improving the water resistance of the membrane. DETAILED DESCRIPTION
[0055] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] In the following specific implementations,
[0057] The mass fraction of polyvinyl alcohol solution is 4%, polyvinyl alcohol CAS number: 9002-89-5, from Nanjing Chemical Reagent Co., Ltd.
[0058] The water-based epoxy resin model is E-51, epoxy value: 0.48-0.54; it comes from Jiangyin Shunsheng Composite Materials Co., Ltd.
[0059] The pigments were sourced from Shenzhen Daxing Chemical Co., Ltd.;
[0060] The etchant is copper etching liquid, model: Q / YS.115, from Guangzhou Yishun Chemical Co., Ltd.
[0061] Green oil solder resist model: CW3300G, from Shanghai Gushuo Electronic Technology Co., Ltd.;
[0062] Graphene oxide, particle size: 10-20 μm, from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;
[0063] The mass fraction of acetic acid solution is 2%, acetic acid CAS number: 64-19-7, from Merck reagent;
[0064] The mass fraction of polyethylene glycol diglycidyl ether solution is 1%, polyethylene glycol diglycidyl ether CAS number: 26403-72-5, from Shanghai Yuanye Biotechnology Co., Ltd.;
[0065] Polyvinyl alcohol CAS number: 9002-89-5, from Guangzhou Hongzhou Chemical Co., Ltd.;
[0066] The silane coupling agent was added in the form of an aqueous solution with a mass fraction of 50%; the silane coupling agent was KH550, which was sourced from Yunsheng Chemical (Shandong) Co., Ltd.;
[0067] Nano-silicon dioxide CAS number: 7631-86-9, particle size: 20nm, purity: 99%, from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;
[0068] Anhydrous ethanol CAS number: 64-17-5, from Jinan Dianhua Chemical Technology Co., Ltd.
[0069] Embodiment 1: A single-sided PCB board and a manufacturing process thereof, comprising the following processes:
[0070] (1) Preparation of anticorrosive ink:
[0071] Mix chitosan and acetic acid solution in a mass ratio of 1:40, and stir until completely dissolved to obtain a chitosan solution;
[0072] The graphene oxide and deionized water were mixed, ultrasonicated for 1 hour until uniformly dispersed, and then chitosan solution was added, stirred and reacted on a magnetic stirrer. After the reaction, the mixture was washed with deionized water until the pH was neutral, and freeze-dried to obtain chitosan-modified graphene oxide powder; the chitosan-modified graphene oxide powder and polyethylene glycol diglycidyl ether solution were mixed in a mass ratio of 1:90, ultrasonically dispersed for 0.5 hour, and then refluxed at 65°C for 4 hours, taken out and washed with deionized water for 3 times, and freeze-dried to obtain modified graphene oxide; the mass ratio of graphene oxide, deionized water, and chitosan solution was 1:90:10; the process conditions of the magnetic stirrer were: temperature: 40°C, duration: 10 hours, speed: 300r / min; the process conditions of freeze-drying were: temperature: -20°C, duration: 20 hours.
[0073] The modified graphene oxide, polyvinyl alcohol, water-based epoxy resin and pigment were mixed in a mass ratio of 2:2:1:1, and stirred on a magnetic stirrer to obtain an anti-corrosion ink; the stirring process conditions of the magnetic stirrer were: temperature: 50°C, duration: 30min, speed: 200r / min;
[0074] (2) Preparation of antioxidant film liquid:
[0075] Nano-silicon dioxide and anhydrous ethanol are mixed in a mass ratio of 1:20, stirred evenly to obtain a mixed solution, and then a silane coupling agent is added, stirred evenly, and refluxed at 65°C for 2.5 hours. After the reaction is completed, it is repeatedly washed and filtered with anhydrous ethanol until the filtrate is clear and transparent. The filter cake is dried at 70°C for 3 hours and then ground into powder to obtain modified nano-silicon dioxide; the mass ratio of the mixed solution to the silane coupling agent is 1:3; the silane coupling agent is added in the form of an aqueous solution with a mass fraction of 50%;
[0076] The polyvinyl alcohol and distilled water were mixed, and magnetic stirring was performed to completely dissolve them. Then, modified nano-silicon dioxide was added, and magnetic stirring was performed. After stirring evenly, ultrasonication was performed for 25 minutes to obtain an antioxidant film liquid. The mass ratio of polyvinyl alcohol, distilled water, and modified nano-silicon dioxide was 1:30:0.3. The process conditions of magnetic stirring were: temperature: 45°C, duration: 55 minutes, and speed: 400 r / min.
[0077] (3) Preparation of PCB single panel:
[0078] S1: Substrate preparation: clean the cut copper-clad laminate to remove dust and burrs from its surface to obtain the substrate; S2: drilling positioning holes: open registration holes at the four corners of the substrate and open circuit holes according to the circuit design; S3: screen printing circuit: print the circuit diagram on the copper-clad side of the substrate with anti-corrosion ink;
[0079] S4: Etching: Soak the printed circuit board in the etchant, stir, corrode the exposed copper sheet, and obtain the circuit layout; S5: Solder mask: Clean the etched substrate, wipe off the moisture, screen print the green oil solder mask, and dry; S6: Quality inspection: Use optical instruments to detect the circuit layout on the substrate obtained in S5, and remove unqualified products; S7: Anti-oxidation: Clean the substrate that has passed the quality inspection, wipe off the moisture, and then apply a layer of anti-oxidation film liquid on the surface, dry it to form a film, and obtain a single-sided PCB; The process conditions for drying in S5 are: temperature: 145℃, duration: 55s; The process conditions for drying in S7 are: temperature 70℃, duration: 1.5h; The process conditions for drying and forming a film are: temperature: 110℃, duration: 2h.
[0080] Embodiment 2: A single-sided PCB board and a manufacturing process thereof, comprising the following processes:
[0081] (1) Preparation of anticorrosive ink:
[0082] Chitosan and acetic acid solution were mixed in a mass ratio of 1:45, and stirred until completely dissolved to obtain a chitosan solution;
[0083] Graphene oxide and deionized water were mixed, ultrasonicated for 1.5 hours until uniformly dispersed, and then chitosan solution was added, stirred and reacted on a magnetic stirrer. After the reaction, the mixture was washed with deionized water until the pH was neutral, and freeze-dried to obtain chitosan-modified graphene oxide powder; chitosan-modified graphene oxide powder and polyethylene glycol diglycidyl ether solution were mixed in a mass ratio of 1:95, ultrasonically dispersed for 1 hour, and then refluxed at 75°C for 5 hours, taken out and washed with deionized water for 4 times, and freeze-dried to obtain modified graphene oxide; the mass ratio of graphene oxide, deionized water, and chitosan solution was 1:95:15; the process conditions of the magnetic stirrer were: temperature: 45°C, duration: 13 hours, speed: 400r / min; the process conditions of freeze-drying were: temperature: -15°C, duration: 22 hours.
[0084] The modified graphene oxide, polyvinyl alcohol, water-based epoxy resin and pigment were mixed in a mass ratio of 3:3:2:1, and stirred on a magnetic stirrer to obtain an anti-corrosion ink; the stirring process conditions of the magnetic stirrer were: temperature: 55°C, duration: 35min, speed: 250r / min;
[0085] (2) Preparation of antioxidant film liquid:
[0086] Nano-silicon dioxide and anhydrous ethanol are mixed in a mass ratio of 1:25, stirred evenly to obtain a mixed solution, and then a silane coupling agent is added, stirred evenly, and refluxed at 70°C for 3 hours. After the reaction is completed, it is repeatedly washed and filtered with anhydrous ethanol until the filtrate is clear and transparent. After the filter cake is dried at 75°C for 4 hours, it is ground into powder to obtain modified nano-silicon dioxide; the mass ratio of the mixed solution to the silane coupling agent is 1:4; the silane coupling agent is added in the form of an aqueous solution, and the mass fraction is 50%;
[0087] The polyvinyl alcohol and distilled water were mixed, magnetically stirred to make them completely dissolved, and then modified nano-silicon dioxide was added, magnetically stirred, and ultrasonicated for 30 minutes after stirring evenly to obtain an antioxidant film liquid; the mass ratio of polyvinyl alcohol, distilled water, and modified nano-silicon dioxide was 1:35:0.4; the process conditions of magnetic stirring were: temperature: 50°C, duration: 60 minutes, and speed: 450r / min;
[0088] (3) Preparation of PCB single panel:
[0089] S1: Substrate preparation: clean the cut copper-clad laminate to remove dust and burrs from its surface to obtain the substrate; S2: drilling positioning holes: open registration holes at the four corners of the substrate and open circuit holes according to the circuit design; S3: screen printing circuit: print the circuit diagram on the copper-clad side of the substrate with anti-corrosion ink;
[0090] S4: Etching: Soak the printed circuit board in the etchant, stir, corrode the exposed copper sheet, and obtain the circuit layout; S5: Solder mask: Clean the etched substrate, wipe off the moisture, screen print the green oil solder mask, and dry; S6: Quality inspection: Use optical instruments to detect the circuit layout on the substrate obtained in S5, and remove unqualified products; S7: Anti-oxidation: Clean the substrate that has passed the quality inspection, wipe off the moisture, and then apply a layer of anti-oxidation film liquid on the surface, dry it to form a film, and obtain a PCB single-sided board; The drying process conditions in S5 are: temperature: 150℃, time: 60s; the drying process conditions are: temperature 90℃, time: 2.5h; the drying film forming process conditions are: temperature: 115℃, time: 3h.
[0091] Embodiment 3: A single-sided PCB board and a manufacturing process thereof, comprising the following processes:
[0092] (1) Preparation of anticorrosive ink:
[0093] Chitosan and acetic acid solution were mixed in a mass ratio of 1:50, and stirred until completely dissolved to obtain a chitosan solution;
[0094] The graphene oxide and deionized water were mixed, ultrasonicated for 2 hours until uniformly dispersed, and then chitosan solution was added, stirred and reacted on a magnetic stirrer. After the reaction, the mixture was washed with deionized water until the pH was neutral, and freeze-dried to obtain chitosan-modified graphene oxide powder; the chitosan-modified graphene oxide powder and polyethylene glycol diglycidyl ether solution were mixed in a mass ratio of 1:100, ultrasonically dispersed for 1.5 hours, and then refluxed at 85°C for 6 hours, taken out and washed with deionized water for 5 times, and freeze-dried to obtain modified graphene oxide; the mass ratio of graphene oxide, deionized water, and chitosan solution was 1:100:20; the process conditions of the magnetic stirrer were: temperature: 50°C, duration: 16 hours, speed: 500r / min; the process conditions of freeze-drying were: temperature: -10°C, duration: 24 hours.
[0095] The modified graphene oxide, polyvinyl alcohol, water-based epoxy resin and pigment were mixed in a mass ratio of 4:4:3:1, and stirred on a magnetic stirrer to obtain an anti-corrosion ink; the stirring process conditions of the magnetic stirrer were: temperature: 60°C, duration: 40min, speed: 300r / min;
[0096] (2) Preparation of antioxidant film liquid:
[0097] Nano-silicon dioxide and anhydrous ethanol are mixed in a mass ratio of 1:30, stirred evenly to obtain a mixed solution, and then a silane coupling agent is added, stirred evenly, and refluxed at 75°C for 3.5 hours. After the reaction is completed, it is repeatedly washed and filtered with anhydrous ethanol until the filtrate is clear and transparent. The filter cake is dried at 80°C for 5 hours and then ground into powder to obtain modified nano-silicon dioxide; the mass ratio of the mixed solution to the silane coupling agent is 1:5; the silane coupling agent is added in the form of an aqueous solution with a mass fraction of 50%;
[0098] The polyvinyl alcohol and distilled water were mixed, and magnetic stirring was performed to completely dissolve them. Then, modified nano-silicon dioxide was added, and magnetic stirring was performed. After stirring evenly, ultrasonication was performed for 35 minutes to obtain an antioxidant film liquid. The mass ratio of polyvinyl alcohol, distilled water, and modified nano-silicon dioxide was 1:40:0.5. The process conditions of magnetic stirring were: temperature: 55°C, duration: 65 minutes, and speed: 500 r / min.
[0099] (3) Preparation of PCB single panel:
[0100] S1: Substrate preparation: clean the cut copper-clad laminate to remove dust and burrs from its surface to obtain the substrate; S2: drilling positioning holes: open registration holes at the four corners of the substrate and open circuit holes according to the circuit design; S3: screen printing circuit: print the circuit diagram on the copper-clad side of the substrate with anti-corrosion ink;
[0101] S4: Etching: Immerse the printed circuit board in the etchant, stir, corrode the exposed copper sheet, and obtain the circuit layout; S5: Solder mask: Clean the etched substrate, wipe off the moisture, screen print the green oil solder mask, and dry; S6: Quality inspection: Use optical instruments to detect the circuit layout on the substrate obtained in S5, and remove unqualified products; S7: Anti-oxidation: Clean the substrate that has passed the quality inspection, wipe off the moisture, and then apply a layer of anti-oxidation film liquid on the surface, dry it to form a film, and obtain a PCB single-sided board; The drying process conditions in S5 are: temperature: 155℃, time: 65s; The drying process conditions are: temperature 110℃, time: 3.5h; The drying process conditions are: temperature: 120℃, time: 4h.
[0102] Comparative Example 1: Compared with Example 1, graphene oxide is not modified when preparing the anti-corrosion ink. A single-sided PCB board and a preparation process thereof include the following processes:
[0103] (1) Preparation of anticorrosive ink:
[0104] Graphene oxide, polyvinyl alcohol, water-based epoxy resin and pigment are mixed in a mass ratio of 2:2:1:1, and stirred on a magnetic stirrer to obtain an anti-corrosion ink; the process conditions of stirring with the magnetic stirrer are: temperature: 50°C, duration: 30min, speed: 200r / min;
[0105] (2) Preparation of antioxidant film solution: the same as in Example 1;
[0106] (3) Preparation of PCB single-sided board: the same as in Example 1.
[0107] Comparative Example 2: Compared with Example 1, when preparing the antioxidant film liquid, the nano-silicon dioxide is not modified. A single-sided PCB board and its preparation process include the following processes:
[0108] (1) Preparation of anticorrosive ink: the same as in Example 1;
[0109] (2) Preparation of antioxidant film liquid:
[0110] The polyvinyl alcohol and distilled water were mixed, and magnetic stirring was performed to completely dissolve them. Then, nano-silicon dioxide was added, and magnetic stirring was performed. After stirring evenly, ultrasonication was performed for 25 minutes to obtain an antioxidant film liquid. The mass ratio of polyvinyl alcohol, distilled water, and nano-silicon dioxide was 1:30:0.3. The process conditions of magnetic stirring were: temperature: 45°C, duration: 55 minutes, and speed: 400 r / min.
[0111] (3) Preparation of PCB single-sided board: the same as in Example 1.
[0112] Comparative Example 3: Compared with Example 1, no modified nano-silicon dioxide is added when preparing the antioxidant film liquid. A single-sided PCB board and its preparation process include the following processes:
[0113] (1) Preparation of anticorrosive ink: the same as in Example 1;
[0114] (2) Preparation of antioxidant film liquid:
[0115] The polyvinyl alcohol and distilled water were mixed, magnetically stirred to make them completely dissolved, and then ultrasonicated for 25 minutes after being stirred evenly to obtain an antioxidant film liquid; the mass ratio of polyvinyl alcohol to distilled water was 1:30; the process conditions of magnetic stirring were: temperature: 45°C, duration: 55 minutes, speed: 400r / min;
[0116] (3) Preparation of PCB single-sided board: the same as in Example 1.
[0117] experiment:
[0118] Take the PCB single-sided boards obtained in Examples 1 to 3 and Comparative Examples 1 to 3 to prepare samples, test their performances respectively and record the test results:
[0119] Corrosion resistance test: immerse the sample in copper etching solution and observe the corrosion of the screen printing ink;
[0120] Water absorption test: According to GB / T1034-2008 "Determination of water absorption of plastics", place the sample in an oven and dry it to constant weight, record the weight as m1, then soak the sample in distilled water for 3 hours, take it out, wipe off the surface moisture with filter paper, record the weight as m2, and the water absorption calculation formula is as follows:
[0121] Water absorption (%) = (m2-m1) × 100 / m1
[0122] Yellowing resistance test: According to GBT2409-1980 "Plastic Yellowness Index Test Method", use YI-48A whiteness colorimeter to test the three stimulus values of PCB single panel samples before and after aging, record them as X, Y, and Z. The calculation formula of the yellowness index of the samples before and after aging is as follows:
[0123] YI=[100×(1.28X-1.06Z)] / Y;
[0124] ΔYI n= YI n -YI0;
[0125] ΔYI n is the change in yellowness index after the sample has aged for n days, YI0, YI n They are the yellowness index values of the sample before aging and after aging for n days. In this test, n=20.
[0126] Corrosion Water absorption (%) Yellow index change Example 1 No rust 1.41 0.54 Example 2 No rust 1.36 0.48 Example 3 No rust 1.29 0.43 Comparative Example 1 Visible rust 1.53 0.59 Comparative Example 2 No obvious rust 1.85 0.68 Comparative Example 3 No obvious rust 2.36 0.83
[0127] According to the data in the above table, we can clearly draw the following conclusions:
[0128] The PCB single-sided board obtained in Examples 1-3 is compared with the PCB single-sided board obtained in Comparative Examples 1-3. The test results show that:
[0129] Compared with Comparative Example 1, the PCB single-sided board obtained in Examples 1 to 3 has better corrosion resistance, antioxidant capacity and lower water absorption, which fully demonstrates that the anti-corrosion ink and antioxidant coating provided in the present invention can improve the corrosion resistance, antioxidant capacity and water resistance of the prepared PCB single-sided board.
[0130] Compared with Example 1, in Comparative Example 1, graphene oxide is not modified when preparing the anti-corrosion ink, and multiple covalent connections cannot be established, and the resistance to corrosive media is reduced; in Comparative Example 2, nano-silicon dioxide is not modified when preparing the antioxidant film liquid, and the nano-silicon dioxide is easy to agglomerate and disperse unevenly, and the water resistance of the antioxidant film is reduced; in Comparative Example 3, no modified nano-silicon dioxide is added when preparing the antioxidant film liquid, the gaps between molecules cannot be filled, the acting force is reduced, the structure is loosely arranged, and the water resistance of the film is significantly reduced; it can be seen that the setting of the process and the materials used in this application can promote the improvement of the corrosion resistance, antioxidant ability and water resistance of the prepared PCB single-sided board.
[0131] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A process for preparing a single-sided PCB board, characterized in that: The following steps are involved: S1: Substrate preparation: Clean the cut copper-clad laminate to remove dust and burrs from its surface to obtain a substrate; S2: Drilling positioning holes: Drilling registration holes at the four corners of the substrate, and opening circuit holes according to the circuit design; S3: Silk-screening circuit: Printing the circuit diagram on the copper-covered side of the substrate with anti-corrosion ink; S4: Etching: Soaking the substrate with the printed circuit diagram in an etchant, stirring, corroding the exposed copper to obtain the circuit layout; S5: Solder mask: Cleaning the etched substrate, wiping off moisture, silk-screening green solder mask, and drying; S6: Quality inspection: Using optical instruments to inspect the circuit layout on the substrate obtained in S5, and removing unqualified products; S7: Anti-oxidation: Clean and dry the substrate that has passed the quality inspection, then apply a layer of anti-oxidation film liquid on the surface, dry it into a film, and obtain a PCB single panel.
2. The process for preparing a single-sided PCB board according to claim 1, characterized in that: The anticorrosive ink described in S3 is prepared by the following process: The modified graphene oxide, polyvinyl alcohol solution, water-based epoxy resin and pigment are mixed in a mass ratio of (2-4):(2-4):(1-3):1, and stirred on a magnetic stirrer to obtain an anti-corrosion ink.
3. The process for preparing a single-sided PCB board according to claim 2, characterized in that: The modified graphene oxide is prepared by the following process: The graphene oxide and deionized water are mixed, ultrasonically dispersed until uniformly dispersed, and then chitosan solution is added, stirred and reacted on a magnetic stirrer. After the reaction is completed, the mixture is washed with deionized water until the pH value is neutral, and freeze-dried to obtain chitosan-modified graphene oxide powder; the chitosan-modified graphene oxide powder and polyethylene glycol diglycidyl ether solution are mixed, ultrasonically dispersed, refluxed, taken out, washed with deionized water for 3 to 5 times, and freeze-dried to obtain modified graphene oxide.
4. The process for preparing a single-sided PCB board according to claim 1, characterized in that: The antioxidant film liquid is prepared by the following process: The polyvinyl alcohol and distilled water are mixed in a mass ratio of 1: (30-40), and magnetically stirred to completely dissolve them. Then, the modified nano-silicon dioxide is added, and magnetically stirred. After stirring evenly, ultrasonication is performed for 25-35 minutes to obtain an antioxidant film liquid.
5. The process for preparing a single-sided PCB board according to claim 4, characterized in that: The modified nano silicon dioxide is prepared by the following process: Mix nano-silica and anhydrous ethanol in a mass ratio of 1: (20-30), stir evenly to obtain a mixed solution, then add a silane coupling agent, stir evenly, and reflux. After the reaction is completed, wash and filter repeatedly with anhydrous ethanol until the filtrate is clear and transparent. After the filter cake is dried, grind it into powder to obtain modified nano-silica.
6. The process for preparing a single-sided PCB board according to claim 2, characterized in that: The process conditions of stirring with a magnetic stirrer are: temperature: 50-60°C, duration: 30-40min, speed: 200-300r / min.
7. The process for preparing a single-sided PCB board according to claim 3, characterized in that: The chitosan solution is prepared by the following process: Chitosan and acetic acid solution are mixed in a mass ratio of 1: (40-50), and stirred until completely dissolved to obtain a chitosan solution.
8. The process for preparing a single-sided PCB board according to claim 4, characterized in that: The process conditions of magnetic stirring are: temperature: 45-55°C, duration: 55-65min, speed: 400-500r / min.
9. The process for preparing a single-sided PCB board according to claim 3, characterized in that: The reflux process conditions are: temperature: 65-85°C, time: 4-6h.
10. A single-sided PCB board, characterized in that: The invention is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation process of printed circuit board
CN116709647A
Cation water-based nano silicon dioxide and preparation method and application thereof
CN101914313A
Long-acting led heat-dissipating coating material and preparation method thereof
CN105131732A
Production method of metal circuit board with high thermal conductivity
CN108243556A
Preparation method for modified graphene / waterborne epoxy resin composite coating
CN110423538A
Cited By
High-speed copper-clad plate resin mixture and preparation method thereof
CN120888164A